Presidents in crisis tough decisions inside the White House from Truman to Obama - Bohn, Michael K (New York Arcade, 2016)
"Every American president, when faced with a crisis, longs to take bold and decisive action. When American lives or vital interests are at stake, the public-and especially the news media and political opponents-expect aggressive leadership. But, contrary to the dramatizations of Hollywood, rarely does a president have that option. In Presidents in Crisis, a former director of the Situation Room takes the reader inside the White House during seventeen grave international emergencies handled by the presidents from Truman to Obama: from North Korea's invasion of South Korea to the revolutions of the Arab Spring, and from the thirteen days of the Cuban Missile Crisis to the taking of American diplomats hostage in Iran and George W. Bush's response to the attacks of September 11, 2001. In narratives that convey the drama of unfolding events and the stakes of confrontation when a misstep can mean catastrophe, he walks us step by step through each crisis. Laying out the key players and personalities and the moral and political calculations that the leaders have had to make, he provides a fascinating insider's look at modern presidential decision making and the fundamental role in it of human frailty. "--
Includes bibliographical references (pages 305-315) and index.
Keywords: Presidents -- United States -- Decision making -- Case studies; Political leadership -- United States -- Case studies; Executive power -- United States -- Case studies; HISTORY / United States / 21st Century; United States -- Foreign relations -- 1945-1989 -- Case studies; United States -- Foreign relations -- 1989- -- Case studies